PTU-150 Simplified Barrett's Radiofrequency Ablation Technique in The Elderly. Consideration Should Be Given to Balancing The Increased Risks with Benefits. (17th August 2016) - Campbell, JA; Hopper, AD
Abstract : Introduction: Barrett's oesophagus (BO) is a major risk factor for the development of oesophageal adenocarcinoma. Radiofrequency ablation (RFA) is an established treatment option in high risk patients with high grade dysplasia (HGD). Recent simplified methods have also been shown to have equivocal treatment success with shorter treatment times. New recommendations to treat patients with low grade dysplasia have been established which will increase numbers of eligible patients. Reduction in procedure duration is attractive to accommodate the increasing referrals, and reduce sedation requirements, especially in the elderly. We aimed to assess the complications and success of simplified RFA technique in consecutive patients undergoing treatment for Barrett's oesophagus. Methods: All patients discharged from simplified RFA treatment course for BO over a 2 year period were identified. Circumferential RFA (c-RFA) or Focal Ultra RFA (u-RFA) was performed with a simplified double application of RFA (12 J/cm) - the device was not removed or cleaned. Simplified Focal RFA (f-RFA) with smaller devices was performed with a (3×15 J/cm no clean) regimen. Strict RFA medication protocol and repeat 3 month follow up was performed for each patient. Patient demographics, success of treatment, withdrawal from treatment and complications were noted. Outcomes were compared in age groups under and over 75 (Fisher's exact test) to assess if there was a difference in complication rate. Results: 36 patients discharged from simplified RFA treatment were identified (11 female; median age 71: range 46–80). 76 treatments were performed in total (22 c-RFA 11 u-RFA and 43 f-RFA). Complete eradication of Barrett's mucosa was successful in 83.3% (30/36) patients. Median number of treatments was 2 (range 1–6). 1 patient with an incomplete response after 4 treatments was treated twice with a non simplified RFA method but after no further response the patient was discharged from RFA programme. 4/36 patients (11.1%) reported complications which resulted in discharging from programme. Reasons were: prolonged atrial-fibrillation with haemodynamic compromise (2 nd treatment u-RFA); significant oesophageal stricture (c-FRA); hypotensive fall with 7 day admission (u-RFA); prolonged post procedure pain (f-RFA). All complications lead to withdrawal from the RFA programme. 30.7% of patients aged over 75 experienced complications compared to 0% in patients under 75 (p = 0.0121). Conclusion: A simplified oesophageal RFA regime is effective to remove BO, however its use in the elderly may be linked with increased complications leading to program withdrawal. Disclosure of Interest: None Declared